AN IN-DEPTH ANALYSIS OF THE POSSIBILITY OF THE PORTRAYAL OF VIOLENCE IN NEWS MEDIA INSTIGATING VIOLENCE IN SOCIETY - ARIA SUSANTH 1, DR. JESUS MILTON ROUSSEAU S 2 (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
This study explores the complex relationship that may exist between how violence is portrayed in the news media and how often violence occurs in society. The portrayal of violence in media has grown more common as it continues to develop, appearing in everything from movies and television shows to video games and internet content. This study intends to investigate the complex relationships between violent media representations and actual violent incidents by critically analysing all the variables in this equation, namely the media, the audience that comprises society and the way the human mind works. The study uses methodology that includes social impact assessments, psychological viewpoints, and content analysis to examine the potential effects of exposure to violent content on people’s attitudes, beliefs, and behaviours. The study aims to find patterns and correlations that could provide insight into the possible causal relationship between societal violence and news media portrayals of violence by closely examining both short- and long-term effects. The purpose of this study is to provide policymakers, media practitioners, and academics who are interested in the societal effects of media content with a deeper understanding of the intricate dynamics between media representations and actual violence. Media and society are reflections of each other and studies have shown how media impacts society. Hence there falls a collective responsibility to understand how media can negatively impact the audience and fix the system to ensure progress. This study aims to add to the current conversation about the effects of news media by providing a comprehensive analysis of the possibility that media portrayals of violence unintentionally trigger violence and vindicate aggression in society.